Designing carbon taxation schemes for automobiles: A simulation exercise for Germany - Adamos Adamou; Sofronis Clerides; Theodoros Zachariadis (Fondazione Eni Enrico Mattei (FEEM), 2011)
Vehicle taxation based on CO2 emissions is increasingly being adopted worldwide in order to shift consumer purchases to low-carbon cars, yet little is known about the effectiveness and overall economic impact of these schemes. We focus on feebate schemes, which impose a fee on high-carbon vehicles and give a rebate to purchasers of low-carbon automobiles. e estimate a discrete choice model of demand for automobiles in Germany and simulate the impact of alternative feebate schemes on emissions, consumer welfare, public revenues and firm profits. The analysis shows that a well-designed scheme can lead to emission reductions without reducing overall welfare.
Keywords: Q5; Q53; Q58; 330; CO2 emissions; German Automobile Market; Feebates; Carbon Taxation; Umweltpolitik; Ökosteuer; Kohlendioxid; Kraftfahrzeugmarkt; Wohlfahrtsanalyse; Deutschland